Do capital controls boost resilence to crises? - Goossens, Roman (2013)
Capital controls are back in vogue and a number of emerging markets reintroduced these measures in recent years in the face of a 'flood' of international capital. Policymakers argue that these tools buttress their economies from the risk of a 'sudden stop' in capital flows. We show that capital controls seem to make emerging market economies (EMEs) more resistant to financial crises (i.e. that output loss following a crisis is lower when controls are higher). However that they also seem to make EMEs more crisis-prone, increasing the probability of crises. Policymakers should hence carefully evaluate whether the benefits of capital controls outweigh the costs before implementing them.